Detecting and Monitoring the Vegetal Cover of Karbala Province (Iraq) Using Change Detection Methods - Muhsin , Israa J.; Mohammed , Amjed H. (Iraqi Journal of Science, 2021)
Karbala province was one of the most important areas in Iraq and considered aneconomic resource of vegetation such as trees of fruits, sieve and other vegetation.This research aimed to utilize change detection for investigating the currentvegetation cover at last three decay. The main objectives of this research are collecta group of studied area (Karbala province) satellite images in sequence time forthe same area, these image captured by Landsat (TM 1995, ETM+ 2005 andLandsat 8 OLI (Operational Land Imager) 2015. Preprocessing such as atmospherecorrection and rectification has been done. Mosaic model between the parts ofstudied area was performing. Gap filling consider being very important step hasbeen implied on the defected image which captured in Landsat 2005. For monitoringthe changes in the studied area, many image processing such as supervisedclassification using Maximum likelihood classifier and support vector machineclassifier have been applied. Target detection using matching filter and changedetection using subtractive method also have been used to detect the change invegetal cover of the studied area. Many histogram and statistical properties wereillustrated as well as the pixel count and the target area has been computed.